Islamic Bank Service Quality and Its Impact on Indonesian Customers’ Satisfaction and Loyalty - Muniaty Aisyah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Islamic bank provides products that conform to sharia. When world financial crisis happened, it did not constrain Islamic banking due to its interest free system. However, in Indonesia, the growth of Islamic bank assets is still in the tenth rank with less than five percent of market share. Customers are still in doubt of its professionalism. Superiority in products and service quality remains in sufficient for customer satisfaction and loyalty. The data sets in this research were analyzed by using path analysis for testing the direct impact and sobel test for indirect impact. The result shows that Islamic bank service quality in Indonesia impacts customer satisfaction and loyalty. However, customer satisfaction does not impact customer loyalty, both directly and indirectly. It means that customers are still dissatisfied with the services provided by Islamic banks. This research recommends strategies for improving service quality and consumer confidence on the distinction of Islamic banking system.DOI: 10.15408/aiq.v10i2.7135